Austrian Economics : the Next Generation. - Horwitz, Steven (Advances in Austrian Economics Ser., 2018)
This book brings together emerging and established scholars to explore the insights that can be gleaned from applying Austrian economics to a range of different topics and a variety of related disciplines, from history to politics to public policy.